Cervicofacial flap revisited - Nakade, Dhananjay V.; Mehta, Jitendra; Zade, Manish; Shahane, Pawan (International Journal of Research in Medical Sciences, 2016)
Background: Cheek defect is difficult to reconstruct .The cervicofacial flap give cosmetically good result with minimum scar and good colour match to the skin and skin texture. It is useful in elderly people because of skin laxity and their scars hidden well in wrinkles. It causes minimal morbidity. Methods: We have studied 12 cases of cervicofacial flap in our series that underwent repair for variety of cheek defects in our hospital from 2012 to 2015. We have used anterior based flaps. We have used subcutaneous flaps in the face and subplatysmal flaps in neck. Their data collected and analysed. Results: In our study mean age was 56 years and male to female ratio was 1:1. Defect size was ranging from 4x7 cms to 7 x 11 cms. The eitiology was trauma in 5 cases, 2 cases of Basal cell Carcinoma, 2 cases of squamous cell carcinoma, 2 cases of angio-neurofibroma and one case of Hemangioma of face. All patients were satisfied with result of cervicofacial flap. FTSG used in four cases accepted very well. Mucosal advancement and z plasty in one case has given good result. PMMC in one case has done to reconstruct cheek. In one case Auricular cartilage used to reconstruct and support lower eyelid. Conclusions: Cervicofacial flap is simple, easy to operate, consume less operating time as compared to microvascular flap. It is less complicated and especially useful in diabetic, hypertensives and old debilitated patients with high risk of anaesthesia.